Pembahasan Formula Hidrolika untuk Pintu-Air-masuk - R. Mohamad Besari (Institute for Research and Community Services (LPPM) ITB, 1972)
The use of coefficient Î¼ or m is well known in hydraulics. However there exist some uncertainties in the value to be assigned in practice. The author costs some doubt on the notion that the some coefficient is used for two similar gates, but which have different flow directions post them. In the present work, the values of the coefficients are determined by conducting experiments in the Hydraulics Laboratory ITB, employing scaled model of a widely used gate in a plume.